Role of ionic liquids in eliminating interfacial defects in mixed matrix membranes - Mannan, H.A. (Elsevier, 2019)
Mixed matrix membranes (MMMs) contain two phases, namely a polymer phase and a dispersed phase. The latter may involve carbon molecular sieve, zeolite activated carbon particles etc. MMMs are considered as the next-generation of industrial gas separation membranes due to the excellent thermal, mechanical and separation properties. However, elimination of interfacial defects in MMMs remains the key challenge in their commercialization and fully exploitation. Ionic liquids have emerged as green solvents and find potential applications in various separation processes. The integration of ionic liquids in MMMs has been considered as a novel approach to overcome the interfacial defects in MMMs. The purpose of this chapter is twofold. First, it provides a review of the general concepts of gas separation membranes including historical development of gas separation membranes, gas separation membrane materials, and mixed matrix membranes. Second, it critically reviews recent developments in ionic liquid infused in the MMMs for eliminating interfacial defects. Future research directions have been identified and briefly deliberated. Â© 2020 Elsevier Ltd. All rights reserved.